Racial attitudes and belief in redeemability: most Whites believe justice-involved Black people can change - Butler, Leah C. (Criminology, 2023)
Public belief in redeemability reduces punitiveness and increases support for policy measures such as rehabilitation, expungement, and housing and employment opportunities. Although racial attitudes are known to influence a wide range of criminal justice policy opinions, their effects on beliefs about redeemability and condemnation have not been fully explored. Using data from a 2019 YouGov survey of a national sample of White U.S. adults (N = 766), the current study estimates the effects of three distinct racial attitudes - racial resentment, racial sympathy, and White nationalism - on three measures of belief in redeemability: 1) a race-neutral measure, 2) a measure of belief in redeemability of Black offenders, and 3) a measure of condemnation of Black offenders. The results indicate that belief in redeemability is high - for offenders in general and for Black offenders. These findings are supported by a second 2022 YouGov survey of White U.S. adults (N = 1,505). Racial sympathy and White nationalism have significant effects across all three outcomes, with the positive effect of White nationalism on condemnation of Black offenders being the largest across the three models. These findings suggest that although most Whites agree that formerly incarcerated people are redeemable, racial attitudes influence these beliefs, especially for Black offenders.